Female Listeners’ Autonomic Responses to Dramatic Shifts Between Loud and Soft Music/Sound Passages: A Study of Heavy Metal Songs - Cheng, Tzu-Han; Tsai, Chen-Gia (Frontiers in Psychology, 2016)
Although music and the emotion it conveys unfold over time, little is known about how listeners respond to shifts in musical emotions. A special technique in heavy metal music utilizes dramatic shifts between loud and soft passages. Loud passages are penetrated by distorted sounds conveying aggression, whereas soft passages are often characterized by a clean, calm singing voice and light accompaniment. The present study used heavy metal songs and soft sea sounds to examine how female listeners’ respiration rates and heart rates responded to the arousal changes associated with auditory stimuli. The high-frequency power of heart rate variability (HF-HRV) was used to assess cardiac parasympathetic activity. The results showed that the soft passages of heavy metal songs and soft sea sounds expressed lower arousal and induced significantly higher HF-HRVs than the loud passages of heavy metal songs. Listeners’ respiration rate was determined by the arousal level of the present music passage, whereas the heart rate was dependent on both the present and preceding passages. Compared with soft sea sounds, the loud music passage led to greater deceleration of the heart rate at the beginning of the following soft music passage. The sea sounds delayed the heart rate acceleration evoked by the following loud music passage. The data provide evidence that sound-induced parasympathetic activity affects listener’s heart rate in response to the following music passage. These findings have potential implications for future research of the temporal dynamics of musical emotions.